2013
DOI: 10.1051/0004-6361/201321900
|View full text |Cite
|
Sign up to set email alerts
|

Non-Zeeman circular polarization of CO rotational lines in SNR IC 443

Abstract: Context. We study interstellar magnetic fields by measuring the polarization in molecular spectral lines and thermal emission of dust. Aims. We report detection of non-Zeeman circular polarization and linear polarization levels of up to 1% in the 12 CO spectral line emission in a shocked molecular clump around the supernova remnant (SNR) IC 443. We examine our polarization results to confirm that the circular polarization signal in CO lines is caused by a conversion of linear to circular polarization, consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…7 and also with XPOl data from the 30m telescope (Hezareh et al 2013). As expected, the correction is largest at the edges of sources with a nearby strong emission peak, because the Stokes beams P j (j = 1, 2, 3) are usually wider than the antenna power beam pattern P 0 , resulting in an increase of the fractional instrumental polarization.…”
Section: Correction For Instrumental Polarizationsupporting
confidence: 66%
“…7 and also with XPOl data from the 30m telescope (Hezareh et al 2013). As expected, the correction is largest at the edges of sources with a nearby strong emission peak, because the Stokes beams P j (j = 1, 2, 3) are usually wider than the antenna power beam pattern P 0 , resulting in an increase of the fractional instrumental polarization.…”
Section: Correction For Instrumental Polarizationsupporting
confidence: 66%
“…It is worth mentioning that Hezareh et al (2013) reported detection of non-Zeeman circular polarization and linear polarization levels of up to 1% in the CO rotational spectral line emission in a shocked molecular clump around the SNR IC 443. They concluded that the non-Zeeman CO circular polarization is most probably due to a linear-tocircular polarization conversion, consistent with a physical model based on anisotropic resonant scattering of Houde et al (2013).…”
Section: Snr Ic 443mentioning
confidence: 98%
“…A similar technique developed to reduce the leakage effect observed with XPOL instrument from the IRAM 30 m telescope is presented in Hezareh et al (2013). In Fig.…”
Section: Instrumental Polarization and Leakagementioning
confidence: 99%